2007
DOI: 10.1063/1.2711374
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of a GaAs-based three-terminal nanowire junction device controlled by double Schottky wrap gates

Abstract: A three-terminal nanowire junction device controlled by double nanometer-sized Schottky wrap gates ͑WPGs͒, which control left and right branches independently, are fabricated utilizing AlGaAs/ GaAs etched nanowires and characterized experimentally. Recently, nanowires have attracted much attention for the next-generation nanodevice materials. Nanowire junctions are important building blocks for nanowire-based devices and their integrated circuits. Rich functionalities were expected theoretically in these syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…Owing to the nonlinearity, the TBJ operates as AND gate by itself [2,3]. Since the nonlinear characteristic is available even at room temperature [2,4], the TBJ device has been widely investigated and has been applied to various analog and digital circuits [3,[5][6][7]. Graphene is an attractive material for the TBJ device because of the ballistic transport owing to the high carrier mobility, which is important for the nonlinear characteristic [1].…”
mentioning
confidence: 99%
“…Owing to the nonlinearity, the TBJ operates as AND gate by itself [2,3]. Since the nonlinear characteristic is available even at room temperature [2,4], the TBJ device has been widely investigated and has been applied to various analog and digital circuits [3,[5][6][7]. Graphene is an attractive material for the TBJ device because of the ballistic transport owing to the high carrier mobility, which is important for the nonlinear characteristic [1].…”
mentioning
confidence: 99%
“…As a possible mechanism occurring in a nonballistic transport regime, we considered the effect of surface potential of the nanowire. 5) We also found that the voltage transfer efficiency of the TBJ can be controlled by attaching Schottky wrap gates (WPGs) on the input branches. 5,6) This device configuration allows its operation as a conventional NOT gate.…”
Section: Introductionmentioning
confidence: 98%
“…5) We also found that the voltage transfer efficiency of the TBJ can be controlled by attaching Schottky wrap gates (WPGs) on the input branches. 5,6) This device configuration allows its operation as a conventional NOT gate. This gives us a new opportunity to implement any Boolean logic function by integrating only TBJs with identical configurations.…”
Section: Introductionmentioning
confidence: 98%
“…A pioneering work by Xu indicates that the nonlinear characteristic appears when the TBJ is operated in the ballistic transport regime 1) . However, experimentally, it is also clearly observed at room temperature (RT) [14][15][16][17][18] where the carrier transport should be in the nonballistic transport regime. The mechanism in such a case has not been clarified yet, although several hypotheses have been introduced, including those regarding the effective mean free path extension 16) and the asymmetric channel depletion due to the surface potential [19][20][21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…The III-V semiconductor nanowire surface is known to behave similarly to a metal gate because high-density surface states fix the surface Fermi level at a certain energy level. From the size dependence of the nonlinear curve 26) and its asymmetric change in the gate-controlled TBJ devices 17,25) , we suppose that this model is applicable to the nonlinear characteristic at RT. To verify the applicability of this model, the identification of the existence of the conductance domain and its portion is necessary.…”
Section: Device Operation and Possible Mechanismsmentioning
confidence: 99%